Users Perception and Factors Affecting Data Quality in Nyarugenge Public Health Facility, Rwanda - Habimana, Bernard; Rutayisire, Erigene (Journal of Public Health International, 2022)
The study evaluated the users' opinions on data quality and related characteristics in ten public-health institutions of Nyarugenge district. A study used a cross-sectional design, data was collected through quantitative (n=150) methodology while qualitative data was obtained using interviews (n=20) and focus group talks (n=3). A checklist was utilized to examine the completeness, accuracy, and timeliness of data quality aspects. Collected quantitative data was analyzed through logistic regression by SPSS to examine the association of variables, while qualitative data was analyzed using the summative content analysis (SCA) to summarize the key themes. A 95 percent confidence level, Odds Ratio (AOR) were used to establish the strength of correlation among study variables, while a p-value of less than (p<0.05) was utilized to identify the variables which were statistically significant associated to HMIS data quality. The study finding showed that the majority (53.0%) was female while, 33 years was an average age, the majority of health practitioner (52.7%) had an A1 diploma. Approximately 90.6% of respondents have a positive perceptions on the system usage. Limited ability and a lack of relevant technology equipment such as computers and the internet have been cited as the challenges while using the system. Factors such as training AOR:2.62(95% CI:1.45, supervision AOR:1.81(95% CI:1.02, AOR:2.50(95% CI:0.85 for education background, works-experience AOR:1.60(95% CI:090 are factors associated with data quality. Maintaining, supportive supervision, regular training and refresher courses should be regularly offered to public health professionals to improve their knowledge in order to maximize the use of health information.
Keywords: Data quality; Health system information system; Perception; HMIS; Rwanda